Carbon–Halogen Bond Activation by Selenium‐Based Chalcogen Bonding. Issue 39 (6th July 2017) - Wonner, Patrick; Vogel, Lukas; Düser, Maximilian; Gomes, Luís; Kniep, Florian; Mallick, Bert; Werz, Daniel B.; Huber, Stefan M.
Abstract: Chalcogen bonding is a little explored noncovalent interaction similar to halogen bonding. This manuscript describes the first application of selenium‐based chalcogen bond donors as Lewis acids in organic synthesis. To this end, the solvolysis of benzhydryl bromide served as a halide abstraction benchmark reaction. Chalcogen bond donors based on a bis(benzimidazolium) core provided rate accelerations relative to the background reactivity by a factor of 20–30. Several comparative experiments provide clear indications that the observed activation is due to chalcogen bonding. The performance of the chalcogen bond donors is superior to that of a related brominated halogen bond donor. Abstract : Activation Se(en) from a different angle : Chalcogen bond donors (chalcogen‐based Lewis acids) accelerate a halide abstraction benchmark reaction by a factor of 20–30. Several comparative experiments provide clear indications that the observed activation is due to chalcogen bonding.